(untitled) - Tracy, John A. (Hoboken, N.J., 2004)
This resource for budding entrepreneurs uses a humorous style to present serious advice on the financial aspects of managing a business. The focus is on making, protecting, and improving profit as well as generating cash flow. All phases in the life of a business are covered, from start-up and stabilization through selling or shutting down. A glossary of accounting and financial terms completes the volume.
Keywords: Business enterprises,Profit,Cash management,Doanh nghiệp kinh doanh,Lợi nhuận,Quản lý tiền mặt; Finance,Management,Tài chính,Quản lý